2020
DOI: 10.3390/su12051981
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Response to Natural and Anthropogenic Factors in Southern Taiwan

Abstract: Global climate change and rapid industrial development have led to changes in streamflow worldwide, and determining the relative contributions from climate variability and human activity is important for water management. However, studies using attribution analysis to investigate the streamflow in Taiwan are scarce. In this study, statistical methods are used to evaluate the changes in streamflow in order to assess the variation in the hydrological environment of Taiwan. Four river basins in Southern Taiwan we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The results of this study were shown to be similar with a previous publication [45], that streamflow variations are mainly due to the climate factor. However, this research extended the study area to almost the whole of southern Taiwan and screened the best fitting Budyko-type equation with given processes.…”
Section: Compared With the Previous Publicationsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study were shown to be similar with a previous publication [45], that streamflow variations are mainly due to the climate factor. However, this research extended the study area to almost the whole of southern Taiwan and screened the best fitting Budyko-type equation with given processes.…”
Section: Compared With the Previous Publicationsupporting
confidence: 91%
“…Evidently, the change of the hydrological environment in southern Taiwan requires more attention to satisfy the future demand for water resources. Yeh and Tsao [45] have already evaluated the attributions of streamflow variations in southern Taiwan. However, just four river basins were selected as study areas in the previous publication, based on the available hydrological and meteorological datasets from gauging stations.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of climate change and anthropogenic factors on hydrological regimes and water resources have been analysed in various regions across the world (Gao et al, 2020; Oliveira et al, 2019; Pirnia et al, 2019; Setti et al, 2020; Shi et al, 2019; Yeh & Tsao, 2020) through these three main approaches: the hydrological model method (Bao et al, 2019), the paired‐basin method (Van Loon et al, 2019), and the time series analysis method (Xu et al, 2014). The hydrological model method quantifies the effects of human activities and climate change on hydrology by fixing the climate scenarios or landscape conditions (Bu et al, 2018; Hu et al, 2020; Liu et al, 2019; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%